14 ÷1/2 - 14/3×9/7
61/3×(2/3+3/4)
(2/3+5/6) ÷3 -(7/9-1/2)
27/12-2/3÷8+7/8
14/5-2/5÷5/4
potrzebuje obliczenia wraz z dzialaniem


Odpowiedź :

Hej!

Twoja odpowiedź znajduje się w załączniku.

Pozdrawiam™

Zobacz obrazek Lombard11

Odpowiedź:

14 : 1/2 - 14/3 * 9/7 = 14 * 2/1 - 2/1 * 3/1 = 28 - 6 = 22

61/3 * (2/3 + 3/4) = 61/3 * (8/12 + 9/12) = 61/3 * 17/12 = 1037/36 = 28 29/36

(2/3 + 5/6) : 3 - (7/9 - 1/2) = (4/6 + 5/6) : 3 - (14/18 - 9/18) =

= 9/6 * 1/3 - (- 5/18) = 9/18 + 5/18 = 14/18 = 7/9

27/12 - 2/3 : 8 + 7/8 = 27/12 - 2/3 * 1/8 + 7/8 = 27/12 - 2/24 + 7/8 =

= 54/24 - 2/24 + 21/24 = 73/24 = 3 1/24

14/5 - 2/5 : 5/4 = 14/5 - 2/5 * 4/5 = 14/5 - 8/25 = 70/25 - 8/25 =

= 62/25 = 2 12/25

Szczegółowe wyjaśnienie: